An integrated approach for building sustainable Islamic social finance ecosystems - Ahmed Tahiri Jouti (ISRA International Journal of Islamic Finance, 2019)
Purpose: Bringing more impact seems to be a real issue for social initiatives and organizations requiring the adoption of new approaches. The paper aims to define an integrated approach for building, maintaining and upgrading Islamic social finance and sustainable ecosystems. Design/methodology/approach The paper presents a conceptual framework based on case studies and literature review describing the methodology and the necessary steps to build sustainable ecosystems. Findings The paper shows the impact of building social finance ecosystems on tackling social issues. It emphasizes the idea that solving social issues is everybody's business - from governments to businesses - and that those initiatives require sufficient Sharīʿah-compliant funding to achieve sustainability goals. Research limitations/implications The paper does not focus on the Islamic world experiences in building ecosystems serving social causes. Practical implications The paper gives an overview on how collaboration between the different social oriented organisations can enhance the social impact of the different initiatives. The aim is to ensure adequate financing to all the ecosystem components during the whole lifecycle. Social implications The suggested approach of building sustainable ecosystems can serve as a way to assess the existing social initiatives and practices to find relevant combinations targeting more impact. Originality/value In the social sphere, the idea of building ecosystems has been explored in different ways but never in a way that gathers all the components including finance providers, coordinators and the different types of initiatives. The paper adapts the ecosystem concept to the Islamic finance specificities.
Keywords: 330; Waqf; Zakat; Islamic social finance; Social finance ecosystems